2017
DOI: 10.5888/pcd14.170328
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Providers’ Level of Preparedness for Recommending Physical Activity to Adults With Disabilities

Abstract: IntroductionAdults with disabilities are more likely to be physically inactive than those without disabilities. Although receiving a health care provider recommendation is associated with physical activity participation in this population, there is little information on factors associated with primary care providers recommending physical activity to patients with disabilities.MethodsWe used 2014 DocStyles data to assess primary care provider characteristics and perceived barriers to and knowledge-related facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Second, further studies should address whether hearing rehabilitation or the use of hearing aids for those with hearing loss can increase physical activity. Third, a previous study 39 showed that there are still approximately 20% of primary care practitioners who do not feel prepared to recommend physical activity to patients with disabilities, including hearing limitation. Our results suggest that those with hearing loss may benefit the most from physical activity because they have lower physical activity level and imply that primary care practitioners should promote physical activity more frequently in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Second, further studies should address whether hearing rehabilitation or the use of hearing aids for those with hearing loss can increase physical activity. Third, a previous study 39 showed that there are still approximately 20% of primary care practitioners who do not feel prepared to recommend physical activity to patients with disabilities, including hearing limitation. Our results suggest that those with hearing loss may benefit the most from physical activity because they have lower physical activity level and imply that primary care practitioners should promote physical activity more frequently in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Appendix B provides legends for all the tables in the paper. Twelve (12) of the 34 studies in this review, explored the perceptions of HCPs practising in Europe [53,[63][64][65][66][67][68][69][70][71][72][73], 10 were conducted in Australia and New Zealand [31,51,69,[74][75][76][77][78][79][80], five each from the UK [52,[81][82][83][84] and USA [85][86][87][88][89], two from Africa [75,90], and one from India [91]. The study designs were varied with 20 of the 34 included studies employing a cross sectional design [31,[65][66][67][68][70][71][72][73][74]76,79,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The other 14 studies explored the perceptions of heterogenous groups of HCPs [30,51,52,63,65,66,71,73,80,82,85,86,91,92]. The HCPs included in these heterogeneous groups included nurses [31,52,53,63,65,66,71,80,82,85,86,92], GPs [52,53,63,65,73,85,91], physicians [53,65,82,86,91], physiotherapists [63,71,73,80,92], dietitians [80,82,92], surgeons [63,80,86], oncologist [31,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…been cited in research, 37,38,46,47) wearable devices, 48,49) public health, [50][51][52][53] and clinical services as well as in primary care. [54][55][56] Kyu et al 28) detailed the dose-response effects of a higher level of physical activity on risk reduction of NCDs and cancers. Moreover, the global recommendations suggest physical activity for 2 or more days per week that strengthens the major muscle groups.…”
Section: Organizing Physical Activity Counseling In Primary Carementioning
confidence: 99%